Benson's Relaxation Therapy and Sleep Quality among Elderlyat a Social Institution in Inakaka, Indonesia - Marasabessy, Nur Baharia; Herawati, Lucky; Achmad, Irhamdi (UI Scholars Hub, 2020)
Serious sleep disturbances among elderlies include attention or memory disorders, depression and often fall. A quasi experimental study design with pre-posttest with control group was performed to determine effect of Benson’s relaxation therapy on sleep quality among the elderly, and influences of sex, age anddisease suffered differences. Of a total of 46 elderlies from a Social Institute in Ambon, 29 were taken for the treatment group and 19 for the control group.The treatment group was interfered with Benson’s breathing relaxation for 14 days. Sleep quality was measured using Pittsburg sleep quality index form. Datawere analyzed using independent t-test and multivariate of variance with signifinat level 0.05. This study found that Benson’s relaxation therapy was able toimprove significantly the elderly sleep quality (p-value = 0.046), and no significant difference between sex, age and disease suffered in elderly sleep quality(p-value > 0.05). The Benson’s relaxation therapy was able to improve the elderly sleep quality especially in Inakaka Social Institution.